Multi-criteria evaluation of renewable and nuclear resources for electricity generation in Kazakhstan. (15th December 2017) - Ahmad, Salman; Nadeem, Abid; Akhanova, Gulzhanat; Houghton, Tom; Muhammad-Sukki, Firdaus
Abstract: Kazakhstan's electricity generation depends heavily on fossil fuels. Renewables and other non-fossil resources provide potential alternatives to diversify the electricity generation system. In this paper, various potential local non-fossil fuel resources, hydro, solar, wind, biomass and uranium are reviewed and an assessment framework for prioritizing these resources is established. A multi-criteria decision making approach, analytic hierarchy process (AHP) based on expert opinion, is utilized for developing the assessment model, using four main criteria of technical, economic, social and environmental aspects and thirteen sub-criteria. The review reveal that Kazakhstan has ample potential to develop a non-fossil fuel based electricity system. Furthermore, the model shows hydro to be the most favorable resource followed by solar; wind and nuclear are ranked third and fourth, respectively while biomass is found to be the least attractive option. It is also found that each resource is inclined towards a particular criterion; hydro towards social, solar towards economic, nuclear towards technical, with biomass and wind directed towards environmental. Besides reporting the use of the AHP model for the first time in the Kazakhstan context, the assessment carried out in this paper can assist decision-makers to articulate long-term energy policy for any country. Highlights: Review 4 renewables and a nuclear resource for electricity generation in Kazakhstan. Present a hierarchy model based on expert elicitation across 13 criteria. Introduce ranking of non-fossil resources in Kazakhstan. Kazakhstan has potential to develop a non-fossil fuel based electricity system.